THE IMPACT OF AI (ARTIFICIAL INTELLEGENGE) ON AUDIT - Ravshanbekov Lazizbek Tolibjon o’g’li; Kuziyeva Dinora Bahodirovna (Modern American Journals, 2025)
This article fully explains the connection between AI and Audit systems in today’s modern world. If we look at the fields of sciences that AI did not get involved, only a few we can count due to its advancements over the period of time. However, it is desirable to know what role Ai is playing in Auditing, and what benefits the auditors can get from applying AI into the process of auditing, especially you may wonder if it is reliable or not to trust AI in sharing internal data of a specific company or letting it detect its frauds and get some clear recommendations to tackle the issues happening in the company’s business cycle.
Keywords: AI, Audit, Accounting system